Why share premises?: the organisational development process of the House for Health - Beller, Annelie; Rutgers, Michael; Thümler, Ekkehard (Voluntary sector review, 2014)
Collaboration among charities has no value in itself; it needs to respond to specific organisational or societal needs. This article draws on a case study of the House for Health, a consortium of five charities in the Netherlands that share premises. It asks how this particular arrangement - can be made instrumental to fostering the charities' missions. We find that its greatest value is to enable collective organisational learning, and discuss implications and options for implementation.
Gesehen am 19.01.2021